Pregabalin for Refractory Radicular Leg Pain due to Lumbar Spinal Stenosis: A Preliminary Prospective Study. (29th March 2016) - Orita, Sumihisa; Yamashita, Masaomi; Eguchi, Yawara; Suzuki, Miyako; Inoue, Gen; Miyagi, Masayuki; Watanabe, Tomoko; Ozawa, Tomoyuki; Kamoda, Hiroto; Ishikawa, Tetsuhiro; Aoki, Yasuchika; Ito, Toshinori; et al.
Abstract : We investigated the efficacy of pregabalin (PGB) for neuropathic leg pain in lumbar spinal stenosis (LSS) patients with disturbed activities of daily living (ADL)/quality of life (QOL) in a prospective observational study. Subjects were a total of 104 LSS patients with neuropathic pain (NeP) in leg and neurological intermittent claudication (IMC) refractory to nonsteroidal anti-inflammatory drugs (NSAIDs) for at least a month. NeP was identified using screening tool, Pain DETECT questionnaire. Visual analog scale (VAS) scores and responses to the Japanese Orthopaedic Association Back Pain Evaluation Questionnaire (JOABPEQ) were assessed before and 6 weeks after PGB treatment initiation. Changes in IMC distance and adverse events were also recorded. PGB significantly improved their VAS scores for pain and sleep quality (P < 0.001 ). With respect to JOABPEQ, significant improvements were observed with regard to the following dimensions: pain-related disorders (P < 0.01 ), lumbar spine dysfunction (P = 0.031 ), gait disturbance (P = 0.028 ), and psychological disorders (P = 0.014 ). The IMC distance showed an improvement tendency after PGB treatment, albeit with no significance (P = 0.063 ). Minor adverse events such as dizziness were observed. PGB can be effective for neuropathic leg pain refractory to NSAIDs in LSS patients, resulting in not only pain control but also improving lower back pain-related ADL/QOL scores.